The Role of Young Performers in Preserving National Musical Heritage - Habibjonova, Shahloxon (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article discusses the importance of national musical heritage and the role of young performers in preserving it. Today, many young people are increasingly interested in modern music. However, traditional music represents our history and identity. Young performers help preserve this heritage by learning, performing, and sharing it with others. The article also provides examples from Uzbekistan and suggests simple ways to support young musicians.